Approach to Patients with Dysphagia: Clinical Insights - Min-Su Kim (Brain Sciences)
Dysphagia is a commonly encountered condition in clinical practice, with a rising incidence reported particularly in South Korea. It can be broadly classified into oropharyngeal dysphagia and esophageal dysphagia, and distinguishing between the two is crucial for establishing rehabilitation treatment strategies. Oropharyngeal dysphagia frequently occurs in central nervous system diseases such as stroke, dementia, and Parkinson’s disease and has a significant impact on prognosis. Additionally, because there is a high risk of life-threatening aspiration pneumonia in patients complaining of dysphagia, an accurate diagnosis must be made during the early stages of the condition. Patients with oropharyngeal dysphagia may report difficulty initiating swallowing and may experience coughing, choking, nasopharyngeal reflux, aspiration, and a sensation of leftover food in the pharynx during swallowing. Patients with esophageal dysphagia may report a sensation of food getting stuck in the esophagus for a few seconds after the initiation of swallowing. Esophageal dysphagia should be characterized by analyzing whether the foods causing dysphagia are solid, liquid, or both, as well as by the progression of symptoms, whether they are progressive or intermittent; their severity; and associated symptoms such as weight loss, heartburn, or regurgitation. Video fluoroscopic swallowing study (VFSS), fiberoptic endoscopic evaluation of swallowing (FEES), and esophagogastroduodenoscopy (EGD) are invaluable in determining the causes, severity, and treatment strategies for dysphagia. Since swallowing disorders are significant factors influencing the course and prognosis regardless of the type of disease, clinicians should adopt a systematic approach to such disorders.